Computer Applications for Staff Development and Patient Education - Hannah, Kathryn J.; Conley-Price, Paula; Fenty, Daryl; McKiel, Elaine; Soltes, Dana; Hogan, Terri; Wiens, Donna (Methods of Information in Medicine, 1989)
The changing and evolving profession of nursing necessitates extensive staff development activities on the part of nursing management. This ongoing responsibility is essential to maintaining the currency and competence of practicing nurses and facilitating their professional growth. Simultaneously there are economic constraints coinciding with increased consumer demands for patient education. The purpose of this paper is to explore an innovative teaching method, the use of instructional computing for staff development and patient education programs. The theoretical frameworks for this instructional modality are identified and general advantages and disadvantages of instructional computing applications are described. Specific examples of programs from the literature are briefly discussed.
Keywords: Education; Computer-Assisted Instruction; Curricula; Health Education